PENGARUH PENERAPAN STRATEGI SQ3R BERBANTUAN MEDIA ILUSTRASI TEKS TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA MATA PELAJARAN BAHASA INDONESIA KELAS V SD KATOLIK GELITING - Christina Febianti; Yohanes Ehe Lawotan; Sonya Kristiani Maria (STKIP Subang, 2026)
This study aimed to determine the effect of implementing the SQ3R strategy assisted by text ulustration media on students’ reading comprehension skills in the Indonesian language subject for Grade V at SD Katolik Geliting. This study employed a quantitative approach using a pre-experimental method with a One Group Pretest-Posttest design. The sample consisted of 22 Grade V students. Data collection techniques included test and observation, with instruments in the form of test items and obsrvation sheets. Data analysis wa conducted using the normality test and hypothesis testing through the paired sample t-test. The result showed that the mean pretest score of 62,27 increased to 79,55 in the posttest. The percentage of students’ learning mastery also increased from 22.73% to 68,18%. The normality test results indicated that the data were normally distributed, thus meeting the requirements for hypothesis testing. Furthermorw, the paired sample t-test resilts showed a significance value of less than 0,05 ( Sig. < 0,05), indicating that H0 was rejected and H1 was accepted. These findings demonstrated that the implementation of the SQ3R strategy assisted by text illustration media had a significant effect on improving students’ reading comprehension skills. Therefore, the SQ3R strategy supported by text illustration media can serve as an effective alternative in enchancing reading comprehension skills, particulary in learning factual and opinion texts at the elementary school level.